Normal Binding of Calcium to Five Fibrinogen Variants with Mutations in the Carboxy Terminal Part of the γ-Chain - Furlan, Miha; Stucki, Bettina; Steinmann, Colette; Jungo, Myriam; Lämmle, Bernhard (Thrombosis and Haemostasis, 1996)
Calcium ions are known to accelerate polymerization of fibrin monomers. Each of the two carboxy terminal domains of normal fibrinogen contains one high-affinity calcium binding site that seems to be situated close to the polymerization site in the γ-chain. Most hitherto described functionally defective fibrinogen variants showed impaired clot formation. Since the tightly bound calcium ions may influence the conformation of the polymerization site, the question arises whether the abnormal clotting of a dysfibrinogen might be due to defective calcium binding. We investigated binding of calcium to fibrinogen and the effect of calcium on the clotting properties of five heterozygous fibrinogen variants showing normal thrombin-induced fibrinopeptide release but abnormal polymerization of fibrin monomers. Each of these dysfibrinogens has one single amino acid substitution in the carboxy-terminal part of the γ-chain: fibrinogen Claro (γ 275 Arg ⟶ His), Milano V (γ 275 Arg Cys), Milano I (γ 330 Asp ⟶ Val), Bern I (γ 337 Asn Lys), and Milano VII (γ 358 Ser Cys). The shortest thrombin clotting time and the earliest onset of turbidity increase were observed in fibrinogen γ 358 Ser ⟶ Cys; both parameters were little affected by calcium concentration. In the variant γ 337 Asn ⟶ Lys, the thrombin time was abnormally prolonged at 0.01 mM Ca2+, but it was normalized at 1 mM calcium. In contrast, the abnormal fibrin polymerization of fibrinogen γ 330 Asp ⟶ Val was barely improved at increasing calcium concentrations. Both variants with the substitution of γ 275 Arg, the residue indispensable for normal D:D interactions, showed the slowest rate of fibrin polymerization and the lowest turbidity of fibrin clots at any Ca2+ concentration used. High affinity calcium binding was found to be normal in all five fibrinogen variants studied, suggesting that their abnormal clotting was not due to defective binding of calcium. The γ-chain in the fragment D1 derived from the variant γ 337 Asn ⟶ Lys was further degraded by plasmin in the presence and in the absence of calcium, whereas fragments D1 from the other four γ-chain variants as well as from normal fibrinogen were protected against plasmic degradation in the presence of 1 mM Ca2+.